MicroRNA‐based risk scoring system to identify early‐stage oral squamous cell carcinoma patients at high‐risk for cancer‐specific mortality. Issue 8 (25th January 2020) - Yoon, Angela J.; Wang, Shuang; Kutler, David I.; Carvajal, Richard D.; Philipone, Elizabeth; Wang, Tian; Peters, Scott M.; LaRoche, Dominic; Hernandez, Brenda Y.; McDowell, Bradley D.; Stewart, Claire R.; Momen‐Heravi, Fatemeh; et al.
Abstract: Background: For early‐stage oral squamous cell carcinoma (OSCC), there is no existing risk‐stratification modality beyond conventional TNM staging system to identify patients at high risk for cancer‐specific mortality. Methods: A total of 568 early‐stage OSCC patients who had surgery only and also with available 5‐year clinical outcomes data were identified. Signature microRNAs (miRNAs) were discovered using deep sequencing analysis and validated by qRT‐PCR. The final 5‐plex prognostic marker panel was utilized to generate a cancer‐specific mortality risk score using the multivariate Cox regression analyses. The prognostic markers were validated in the internal and external validation cohorts. Results: The risk score from the 5‐plex marker panel consisting of miRNAs‐127‐3p, 4736, 655‐3p, TNM stage and histologic grading stratified patients into four risk categories. Compared to the low‐risk group, the high‐risk group had 23‐fold increased mortality risk (hazard ratio 23, 95% confidence interval 13‐42), with a median time‐to‐recurrence of 6 months and time‐to‐death of 11 months (vs >60 months for each among low‐risk patient; p < .001). Conclusion: The miRNA‐based 5‐plex marker panel driven mortality risk score formula provides clinically practical and reliable measures to assess the prognosis of patients assigned to an early‐stage OSCC.